Long-Term Analysis of Pertussis Vaccine Immunity to Identify Potential Markers of Vaccine-Induced Memory Associated With Whole Cell But Not Acellular Pertussis Immunization in Mice - Weaver, Kelly L.; Blackwood, Catherine B.; Horspool, Alexander M.; Pyles, Gage M.; Sen-Kilic, Emel; Grayson, Emily M.; Huckaby, Annalisa B.; Witt, William T.; DeJong, Megan A.; Wolf, M. Allison; Damron, F. Heath; Barbier, Mariette (Frontiers in Immunology, 2022)
Over two decades ago acellular pertussis vaccines (aP) replaced whole cell pertussis vaccines (wP) in several countries. Since then, a resurgence in pertussis has been observed, which is hypothesized to be linked to waning immunity. To better understand why waning immunity occurs, we developed a long-term outbred CD1 mouse model to conduct the longest murine pertussis vaccine studies to date, spanning out to 532 days post primary immunization. Vaccine-induced memory results from follicular responses and germinal center formation; therefore, cell populations and cytokines involved with memory were measured alongside protection from challenge. Both aP and wP immunization elicit protection from intranasal challenge and generation of pertussis specific antibody responses in mice. Responses to wP vaccination were characterized by a significant increase in T follicular helper cells in the draining lymph nodes and CXCL13 levels in sera compared to aP mice. In addition, a population of B. pertussis+ memory B cells was found to be unique to wP vaccinated mice. This population peaked post-boost, and was measurable out to day 365 post-vaccination. Anti-B. pertussis and anti-pertussis toxoid antibody secreting cells increased one day after boost and remained high at day 532. The data suggest that follicular responses, and in particular CXCL13 levels in sera, could be monitored in pre-clinical and clinical studies for the development of the next-generation pertussis vaccines.